Innovative pilot plant capacitive deionization for desalination brackish water - Zaid S. Alotaibi; Khalid N. Alharbi; Yaseen Alharbi; Mohammed S. Almoiqli (Applied Water Science, 2024)
Abstract A semi-industrial demineralization facility was used in six CDI cells to desalinate in two steps. A desalination cycle lowered the feedwater salinity from 1 to 0.5 g/L and produced 200 l/h of demineralized water. This process may be repeated to increase efficiency. Initially, feedwater commenced at 1 g/L. Monitoring both voltage and current during the salt ion removal indicated that CDI cells may recover 30% of the energy utilized. Furthermore, V–Q curves using charge and voltage measurements increased energy recovery by 30%. By cutting off the CDI cells' power source, the electrodes' operating voltage was recorded between 0.85 and 0.9 V, much lower than the external contacts' 1.2 V. The desalination system's efficiency could rise if the electrode voltage was measured and adjusted. In conclusion, storage tanks can provide desalinated water while minimizing water waste; hence, they should be installed. This study examined the physical–technical parameters of a CDI desalination system through experiments and several operational modes. Moreover, it revealed CDI desalination system improvements.